Perancangan Sistem Informasi Penjualan Produk Hasil Daur Ulang Sampah Berbasis Website Dengan Pendekatan Metode Waterfall - Ika Yuniva; Andriansah Andriansah; Ditha Julia Maulina (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2018)
In the process of selling recycled waste made by PKK (Family Welfare Development) mothers, Gebang Raya Tangerang Village still uses a manual system, by utilizing sales at various exhibition activities or around the neighborhood, thus allowing a lack of extensive promotion and errors in recording sales data. The purpose of this study is to produce a website for selling recycled waste products as a marketing medium and helping PKK Gebang Raya women to increase sales. With the design of this information system sales system for recycling recycled products, it can help PKK women in Gebang Raya Village to promote waste recycling products through the internet. The form of this research is in the form of case studies with methods of observation and literature in collecting the data needed. Whereas the system requirements in designing information systems for selling products based on recycling of waste based on this website are web administrators who can process product recycled waste, display product data and process product deletion and change purchase status. Whereas the user can order recycled waste products, view waste recycling products, register as a member, and confirm payment. The author uses the waterfall model approach as a method of software development. The data model is described by ERD (Entity Relationship Diagram) and LRS (Logical Record Structure) while the database uses MySQL and the programming language uses PHP.